ChemInform Abstract: Bifunctional Amine‐Squaramides: Powerful Hydrogen‐Bonding Organocatalysts for Asymmetric Domino/Cascade Reactions. Issue 16 (April 2015) - Chauhan, Pankaj; Mahajan, Suruchi; Kaya, Ugur; Hack, Daniel; Enders, Dieter
Abstract Review: [93 refs.